Soil respiration measured with soil flux chamber LI-6400-09 – effects of soil temperature - Irena MAČEK; Dominik VODNIK; Franc BATIČ (Acta Agriculturae Slovenica)
The rate of exchange of CO2 between soil and atmosphere is controlled by atmospheric and soil physical and biological conditions. Predominant processes that produce carbon dioxide in soil are root and soil organism respiration and decomposition of organic matter. In our research, soil CO2 efflux in homogeneous soil samples was measured with dynamic chamber system LI-6400-09 employing infrared gas analyzer (IRGA). Simultaneously, soil and air temperature were measured and the data were later correlated with soil respiration. The measurements were performed at different day periods and at different weather conditions in order to determine the optimal measurement conditions. CO2 efflux was significantly lower (0.70 ± 0.14 m mol m-2 h-1) when measured in the morning with average soil temperature (12.2 ± 1.7 oC), compared to the measurements during the cloudy day with efflux (1.44 ± 0.23 m mol m-2 h-1), average soil temperature (16.4 ± 0.8 oC) and the sunny day efflux (2.24 ± 0.38 m mol m-2 h-1) with the highest average soil temperatures (21.2 ± 3.2 oC). The soil temperature accounted for 80.1 % of soil respiration variability. The Q10 value, calculated for soil CO2 efflux was 2.3. Thus, to collect an appropriate amount of comparable data replications, required due to high soil spatial variability, soil respiration measurements should be performed at relatively stable atmospheric conditions. The comparable flux measurements should be taken always at the same day period.